POD resin material, POD resin film, preparation method of POD resin film, graphite film and electronic equipment
Through the carbonization and graphitization treatment of POD resin materials with a specific molar ratio, a graphite film with high thermal conductivity is formed, which solves the problems of poor thermal conductivity and large powder loss in the existing graphite film, and achieves high thermal conductivity and low powder loss. Both effects.
Patent Information
- Application Number
- CN202310817704.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-05
- Publication Date
- 2025-01-07
AI Technical Summary
The existing artificial graphite thermal film has low thickness, poor thermal conductivity and easy to break, and the thermal conductivity of aromatic polyoxadiazole resin has not been significantly improved after graphitization of carbide, and the powder drop is high, so it cannot be effectively used in electronic equipment. Heat dissipation.
Using a specific molar ratio of POD resin materials, including repeating units A, B and C, a graphite film with high thermal conductivity is formed by carbonization and graphitization, which increases the stability and flexibility of the material, and forms a stable during the graphitization process. C six-membered ring structure reduces the amount of powder loss.
The obtained graphite film has a high thermal conductivity and low powder loss on the surface, which can effectively protect the heat export of electronic equipment, reduce pollution to the equipment, and has both high thermal conductivity and low powder loss.
Smart Images

Figure CN119264424A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of thin film materials, and in particular to a POD resin material, a POD resin film and a preparation method thereof, a graphite film and an electronic device. Background Art
[0002] With the improvement of electronic equipment performance and the continuous miniaturization of products, higher requirements are placed on the heat dissipation of electronic equipment. For miniaturized electronic equipment, since the internal electronic components are constrained by space, they can generally only dissipate heat through the outer shell. The heat conduction between the electronic components and the outer shell is crucial to the heat dissipation of the electronic components. Selecting a suitable thermal conductive material between the electronic components and the outer shell for heat conduction can help to quickly dissipate heat. Artificial graphite is often widely used in various fields due to its strong thermal conductivity and large-scale production and processing. Existing artificial graphite often uses polyimide (PI) as the base material, and artificial graphite can be obtained by carbonizing and graphitizing PI. However, the artificial graphite obtained with PI as the base material has a low thickness, low thermal conductivity, and poor bendability. When used as a thermal conductive film, it is easy to cause poor thermal conductivity and easy fracture. In order to solve the above problems, it is necessary to develop new polymer materials to prepare artificial graphite. Aromatic polyoxadiazole (POD) is a high-performance polymer containing benzene rings and oxadiazole rings on the molecular chain. Artificial graphite can be obtained by carbonizing and graphitizing aromatic polyoxadiazole films. However, the thermal conductivity of artificial graphite obtained using currently disclosed aromatic polyoxadiazole polymer materials has not been significantly improved, and the amount of powder shedding is also high, making it unusable as a thermal conductive material. Summary of the invention
[0003] The present application provides a POD resin material, a POD resin film and a preparation method thereof, a graphite film and an electronic device to improve the thermal conductivity of artificial graphite and reduce the amount of powder loss of artificial graphite.
[0004] In a first aspect, the present application provides a POD resin material, wherein the POD resin film comprises a repeating unit A, a repeating unit B and a repeating unit C, and the structures of the repeating unit A, the repeating unit B and the repeating unit C are as follows:
[0005]
[0006] Wherein, Ar1 is selected from a substituted or unsubstituted aromatic ring group of 6 to 20 carbon atoms;
[0007] Ar2 is a substituted or unsubstituted aromatic ring group containing two benzene rings;
[0008] Ar3 is selected from a substituted or unsubstituted aromatic ring group of 6 to 20 carbon atoms, and at least one hydrogen in the aromatic ring group is substituted by a sulfonic acid group;
[0009] The molar ratio of the number of moles of the repeating unit A to the sum of the number of moles of the repeating unit B and the repeating unit C is 99:1 to 70:30;
[0010] The molar ratio of the repeating unit B to the repeating unit C is 1:1 to 2:1.
[0011] The POD resin material of the present application contains repeating units A, B and C in its molecular structure, and the repeating units A, B and C satisfy a specific molar ratio. The POD resin having the above molecular structure can increase the flexibility of the POD resin and the surface flatness of the material when forming a POD resin film. After carbonization and graphitization, the obtained graphite film has higher stability, and the obtained graphite film has a higher thermal conductivity and is not easy to fall off. When used as a thermally conductive film, it can effectively protect the heat of electronic equipment from being exported in time, and reduce the pollution of the graphite film to the electronic equipment.
[0012] In an optional implementation, Ar1 is selected from phenyl, biphenyl or naphthyl; Ar2 is selected from biphenyl, naphthyl, Br-substituted biphenyl or Br-substituted naphthyl; Ar3 is selected from phenyl, biphenyl or naphthyl substituted with sulfonic acid.
[0013] In an optional implementation, in the POD resin material, the mass proportion of C element is ≥40%, and the mass proportion of S element is ≤10%. If the content of C element is too low, the thermal conductivity of the final graphite film will be affected. If the mass proportion of C is high, a higher quality graphite film can be obtained in the same mass of POD resin film.
[0014] In an optional implementation, the molar ratio of the benzene ring to the oxadiazole ring is 1:1.1 to 1:1.5. The oxadiazole rings in this molar ratio can form a stable pyrrole structure during the heat treatment process, and the formed pyrrole structure can be conducive to forming a stable C6-ring structure during the graphitization process, thereby improving the thermal conductivity of the graphite thermal conductive film.
[0015] In an optional implementation, the POD resin material contains graphene, wherein the mass proportion of the graphene in the POD resin material is 0.5%-50%. Graphene has a high thermal conductivity, and therefore, by adding graphene to the POD resin, a graphite film with higher thermal conductivity can be obtained after the POD resin material is carbonized.
[0016] In a second aspect, the present application provides a POD resin film, which is prepared from the POD resin material of the present application.
[0017] In a third aspect, the present application provides a method for preparing a POD resin film, the preparation method comprising:
[0018] placing a reaction raw material comprising an aromatic diacid monomer, an aromatic diformic acid sulfonate and a hydrazine salt monomer in a fuming sulfuric acid solution for polymerization reaction to obtain a resin solution; and subjecting the resin solution to a film-forming treatment to obtain the POD resin film;
[0019] The aromatic diacid monomers include at least some diphenyl ring aromatic diacid monomers, and the ratio of the total molar number of the aromatic diacid monomers and the aromatic diformic acid sulfonate to the molar number of the hydrazine salt is 1:1.01 to 1:1.1.
[0020] Part of the aromatic diacid monomers reacts with hydrazine salt to form repeating unit A, the diphenyl ring aromatic diacid monomers in the aromatic diacid monomers reacts with hydrazine salt to form repeating unit B, and the aromatic dicarboxylic acid sulfonate reacts with hydrazine salt to form repeating unit C.
[0021] In an optional implementation, the viscosity of the resin solution is greater than 100 Pa.S, and the solid content is 5-20%. The viscosity and solid content of the resin solution affect the molding quality of the film. If the viscosity of the resin solution is too low, the roller sticking phenomenon is serious, and the film surface of the film is not smooth; the solid content affects the viscosity of the POD resin solution. At the same time, if the solid content is too low, the solvent accounts for a high proportion, and the economic efficiency is poor.
[0022] In an optional implementation, the aromatic diacid monomer includes at least two of terephthalic acid, 1,4-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, 3,3-biphenyl dicarboxylic acid, terephthalic acid, 2,4-biphenyl dicarboxylic acid, 3,3-diphenyl ether dicarboxylic acid, isophthalic acid, biphenyl dicarboxylic acid, 2,6-naphthalene dicarboxylic acid or 1,4-naphthalene dicarboxylic acid; at least one of which is a diphenyl ring aromatic diacid monomer. The diphenyl ring aromatic diacid monomer can be selected from at least one of biphenyl dicarboxylic acid, 2,6-naphthalene dicarboxylic acid or 1,4-naphthalene dicarboxylic acid.
[0023] In an optional implementation, the aromatic dicarboxylic acid sulfonate includes a combination of isophthalic acid-5-sulfonate.
[0024] In an optional implementation, the polymerization reaction includes: prepolymerization at 80-110° C. for 2-5 hours, and then heating to 110-170° C. for polymerization for 2-5 hours. This polymerization process can help form a stable network structure, which helps to improve the integrity and stability of the graphite film structure in the subsequent carbonization and graphitization processes.
[0025] In a fourth aspect, the present application provides a graphite film, and the POD resin film of the present application is obtained by carbonization and graphitization treatment; the thickness of the graphite film is 0.01mm~100mm, the thermal conductivity coefficient is ≥1300W / m*k, and the surface powder loss is ≤2mg.
[0026] In an optional implementation, the carbonization temperature in the carbonization treatment is 800-1400°C, and the heating rate is 0.1-1°C / min. In an implementation, in the carbonization treatment, the heating rate is 0.4-0.8°C / min in the range of 800-1000°C; and the heating rate is 0.1-0.4°C / min in the range of 1000-1400°C. This process is conducive to reducing film surface cracks of the resin film and effectively reducing surface powder loss of the graphite film.
[0027] In a fifth aspect, the present application provides an electronic device, comprising a housing, a heating device and a graphite film as described in the present application, wherein the graphite film is disposed between the housing and the heating device.
[0028] The technical effects that can be achieved by the second to fifth aspects mentioned above can be described with reference to the corresponding effects in the first aspect mentioned above, and will not be repeated here.
[0029] Among them, the data in the above-mentioned possible implementation methods of the present application, such as the molar ratio of each repeating unit, the molar ratio of each raw material, and the temperature, time, heating rate and performance parameters in the preparation method, when measuring, the values within the scope of engineering measurement error should be understood to be within the scope specified in the present application. DETAILED DESCRIPTION
[0030] In order to make the objectives, technical solutions and advantages of the present application clearer, the present application is described in further detail below.
[0031] The terms used in the following embodiments are only for the purpose of describing specific embodiments and are not intended to be limiting of the present application. As used in the specification and appended claims of the present application, the singular expressions "a", "an", "above", "the" and "this" are intended to also include expressions such as "one or more", unless there is a clear contrary indication in the context.
[0032] References to "one embodiment" or "some embodiments" etc. described in this specification mean that a particular feature, structure or characteristic described in conjunction with the embodiment is included in one or more embodiments of the present application. Thus, the phrases "in one embodiment", "in some embodiments", "in some other embodiments", "in some other embodiments", etc. that appear at different places in this specification do not necessarily refer to the same embodiment, but mean "one or more but not all embodiments", unless otherwise specifically emphasized in other ways. The terms "including", "comprising", "having" and their variations all mean "including but not limited to", unless otherwise specifically emphasized in other ways.
[0033] The POD resin material of the embodiment of the present application contains a specific ratio of repeating unit A, repeating unit B and repeating unit C in its molecular structure. By using the POD resin material of the embodiment of the present application as a raw material and subjecting it to carbonization and graphitization treatment, a graphite film with good thermal conductivity and not easy to fall off can be obtained. The POD resin material of the embodiment of the present application is further described in detail below.
[0034] A POD resin material according to an embodiment of the present application includes a repeating unit A, a repeating unit B, and a repeating unit C. The structures of the repeating unit A, the repeating unit B, and the repeating unit C are as follows:
[0035]
[0036] In one embodiment, the molecular formula of the POD resin material can be expressed by the following chemical formula:
[0037]
[0038] Wherein, the ratio n1:(n2+n3) of the molar number n1 of repeating unit A to the sum of the molar numbers of repeating unit B and repeating unit C is in the range of 99:1 to 70:30. For example, the ratio n1:(n2+n3) can be, for example, 99:1, 95:5, 90:10, 88:12, 85:15, 80:20, 78:22, 75:25, 70:30 or a value between any two of the above ratios.
[0039] The ratio of the molar number n2 of the repeating unit B to the molar number n3 of the repeating unit C is 1:1 to 2:1. For example, the ratio of n2:n3 can be 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2:1 or a value between any two of the above ratios.
[0040] It can be understood that the above molecular formula is only used to characterize the repeating unit A, repeating unit B and repeating unit C containing the above molar number in the molecular structure, and does not mean that the repeating unit A, repeating unit B and repeating unit C are connected and arranged according to the above structure.
[0041] In the molecular structure of the POD resin material, Ar1 is selected from a substituted or unsubstituted aromatic ring group of 6 to 20 carbon atoms. For example, Ar1 can be selected from a phenyl group, a biphenyl group or a naphthyl group.
[0042] Ar2 is a substituted or unsubstituted aromatic ring group containing two benzene rings, and Ar1 and Ar2 are different. For example, Ar2 can be selected from biphenyl or naphthyl, or Br-substituted biphenyl or Br-substituted naphthyl.
[0043] Ar3 is selected from a substituted or unsubstituted aromatic ring group of 6-20 carbon atoms and at least one hydrogen in the aromatic ring group is substituted by a sulfonic acid group. For example, Ar3 can be selected from a phenyl, biphenyl or naphthyl group substituted by a sulfonic acid group.
[0044] Among them, in the POD resin material of the embodiment of the present application, the mass proportion of the C element is ≥40%. Exemplarily, the mass proportion of the C element can be, for example, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or 90% or a value between any two of the above values. The mass proportion of the S element is ≤10%. Exemplarily, the mass proportion of the S element can be, for example, 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3% or a value between any two of the above values.
[0045] In the POD resin material of the embodiment of the present application, the molar ratio of the benzene ring to the oxadiazole ring in its molecular structure is 1:1.1 to 1:1.5. For example, the molar ratio of the benzene ring to the oxadiazole ring can be, for example, 1:1.1, 1:1.2, 1:1.3, 1:1.4 or 1:1.5 or a value between any two of the above values.
[0046] In order to improve the thermal conductivity of the graphite film formed after the graphitization of the POD resin material, graphene can be added to the POD resin material. Among them, the mass proportion of graphene in the POD resin material is 0.5%-50%. Exemplarily, the mass proportion of graphene in the POD resin material can be, for example, 0.5%, 1%, 2%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% or 50% or a value between any two of the above values.
[0047] Based on the same technical purpose, an embodiment of the present application provides a POD resin film, which is prepared from the POD resin material of the present application.
[0048] Among them, the preparation method of the POD resin film of the embodiment of the present application includes the following steps: placing the reaction raw materials containing aromatic diacid monomers, aromatic dicarboxylic acid sulfonates and hydrazine salt monomers in a fuming sulfuric acid solution for polymerization reaction to obtain a resin solution; the resin solution is subjected to film-forming treatment to obtain the POD resin film; wherein the aromatic diacid monomers at least include a portion of diphenyl ring aromatic diacid monomers, and the ratio of the total molar number of the aromatic diacid monomers and the aromatic dicarboxylic acid sulfonates to the molar number of the hydrazine salt is 1:1.01 to 1:1.1.
[0049] Part of the aromatic diacid monomers react with the hydrazine salt monomers to form repeating unit A, the diphenyl ring aromatic diacid monomers in the aromatic diacid monomers react with the hydrazine salt monomers to form repeating unit B, and the aromatic dicarboxylic acid sulfonate reacts with the hydrazine salt monomers to form repeating unit C.
[0050] Among them, the aromatic diacid monomer includes at least two of terephthalic acid, 1,4-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, 3,3-biphenyl dicarboxylic acid, terephthalic acid, 2,4-biphenyl dicarboxylic acid, 3,3-diphenyl ether dicarboxylic acid, isophthalic acid, biphenyl dicarboxylic acid, 2,6-naphthalene dicarboxylic acid or 1,4-naphthalene dicarboxylic acid; at least one of them is a diphenyl ring aromatic diacid monomer. The diphenyl ring aromatic diacid monomer can be selected from at least one of biphenyl dicarboxylic acid, 2,6-naphthalene dicarboxylic acid or 1,4-naphthalene dicarboxylic acid. The aromatic dicarboxylic acid sulfonate includes isophthalic acid-5 sulfonate. For example, isophthalic acid-5 sulfonate can be calcium isophthalic acid-5 sulfonate.
[0051] The polymerization reaction of each reaction raw material in fuming sulfuric acid includes the following process: prepolymerization at 80-110°C for 2-5 hours, and then heating to 110-170°C for polymerization for 2-5 hours. The viscosity of the resin solution obtained after the polymerization reaction of each reaction raw material is greater than 100 Pa.S, and the solid content is 5-20%.
[0052] The resin solution is subjected to a film-forming treatment to obtain a POD resin film, wherein the film-forming treatment may include the following steps: degassing, casting, stretching, drying and shaping processes.
[0053] The embodiment of the present application also provides a graphite film, which uses the POD resin film of the present application as a raw material, and the POD resin film is obtained by carbonization and graphitization. Among them, the carbonization temperature in the carbonization treatment can be 800-1400°C, and the heating rate can be 0.1-1°C / min. In a specific embodiment, in the carbonization treatment, when the temperature rises to the range of 800-1000°C, the heating rate can be 0.4-0.8°C / min; when the temperature rises to the range of 1000-1400°C, the heating rate can be 0.1-0.4°C / min. In the graphitization treatment, when the temperature rises to the range of 1400-2000°C, the heating rate can be 2-5°C / min; when the temperature is in the range of 2000-2800°C, the heating rate can be 3-8°C / min. This process is conducive to reducing the film surface cracks of the resin film and effectively reducing the surface powder loss of the graphite film.
[0054] The thickness of the graphite film of the embodiment of the present application can be 0.01mm to 100mm. The thickness of the graphite film obtained by the method of the present application can be adjusted in a relatively large range, and both micron-level films and millimeter-level films with large thickness can be obtained. The thermal conductivity of the obtained graphite film can be ≥1300W / m*k, and the surface powder loss can be ≤2mg. Therefore, the graphite film of the embodiment of the present application can have the advantages of high thermal conductivity and low drop amount.
[0055] The embodiment of the present application also provides an electronic device, which may include a housing, a heating device, and a graphite film of the embodiment of the present application. The graphite film is arranged between the housing and the heating device to conduct the heat of the heating device. Exemplarily, the graphite film may be attached to the surface of the heating device, may be attached to the inner wall of the housing, and may be filled in the gap between the heating device and the housing to timely conduct the heat generated by the heating device.
[0056] The POD resin film of the present application will be further described in detail below in conjunction with specific embodiments.
[0057] Examples 1-5 and Comparative Examples 1-5
[0058] The preparation process of POD resin film includes the following steps:
[0059] S1. Aromatic diacid monomer, diphenyl ring aromatic diacid monomer, aromatic diformic acid sulfonate and hydrazine salt monomer are used as reaction raw materials, and polycondensation reaction is carried out in fuming sulfuric acid to obtain a resin solution; the viscosity of the resin solution is greater than 100 Pa.S, and the solid content is 5-20%.
[0060] S2. The resin solution is extruded through a hanger-type die, and then transported in sequence to the first-stage coagulation bath (reaction temperature is 90-130°C, reaction time is 3-5h), the second-stage coagulation bath (reaction temperature is 140-170°C, reaction time is 2-6h) and the third-stage coagulation bath (reaction temperature is 150-180°C, reaction time is 3-6h) for coagulation molding to obtain a coagulated acid-containing wet primary cast film, wherein each stage of the coagulation bath includes sulfuric acid and water.
[0061] S3, washing the acid-containing wet primary cast film to obtain a primary cast film free of sulfuric acid;
[0062] S4. After biaxially stretching the raw cast film that does not contain sulfuric acid, heat-setting treatment is performed at 300-450° C., and edge trimming and winding are performed to obtain a POD resin film.
[0063] The raw materials and molar amounts of the raw materials used in Examples 1-5 and Comparative Examples 1-5 are listed in Table 1.
[0064] Table 1
[0065]
[0066] Examples 6-10 and Comparative Examples 6-10
[0067] The POD resin films of Examples 1-5 and Comparative Examples 1-5 were subjected to carbonization and graphitization to obtain graphite films. The POD resin films corresponding to Examples 1-5 and Comparative Examples 1-5 were subjected to the following processes to obtain graphite films, which were respectively recorded as Examples 6-10 and Comparative Examples 6-10.
[0068] Carbonization treatment process: When the room temperature rises to 800°C, the heating rate is controlled at 0.8-1°C / min; in the range of 800-1000°C, the heating rate is controlled at 0.4-0.8°C / min; when the temperature rises to the range of 1000-1400°C, the heating rate can be 0.1-0.4°C / min.
[0069] Graphitization treatment process: when the temperature is in the range of 1400-2000°C, the heating rate can be 2-5°C / min; when the temperature is in the range of 2000-2800°C, the heating rate can be 3-5°C / min.
[0070] Embodiment 11
[0071] The POD resin material of Example 1 is subjected to the following carbonization and graphitization process to form a graphite film.
[0072] Carbonization treatment process: When the room temperature rises to 800°C, the heating rate is controlled at 5°C / min; in the range of 800-1000°C, the heating rate is controlled at 3°C / min; when the temperature rises to the range of 1000-1400°C, the heating rate can be 2°C / min.
[0073] Graphitization treatment process: when the temperature is in the range of 1400-2000°C, the heating rate can be 2-5°C / min; when the temperature is in the range of 2000-2800°C, the heating rate can be 3-5°C / min.
[0074] The thermal conductivity of the graphite films of each embodiment and comparative example and the amount of powder loss of the graphite films corresponding to embodiments 6-10 and comparative examples 6-10 were tested respectively. The test results are listed in Table 2.
[0075] The thermal conductivity test method includes: using a heat flow sensor to measure the heat flow through the sample to obtain the thermal conductivity of the sample.
[0076] The test method for the powder loss includes: selecting a protective film of 1-2gf / 25mm with a size of 50*130mm; the size of the sample graphite film is 50*100mm. Remove the transparent release film from the test protective film and weigh it, and record the weight t1. A single-sided adhesive is attached to the head and tail of the graphite film and fixed to the stainless steel plate, and the overlapping width of the single-sided adhesive and the graphite film is 5mm. Use a 2Kg roller to roll 3 times, with a rolling speed of (600±10)mm / min; let it stand for 10min; peel off the protective film in the opposite direction at an angle of 180°, with a stretching speed of 300±10mm / min, and peel off the protective film from the surface of the graphite film; weigh the peeled protective film, record the weight t2, and the mass change △t is the powder loss weight, △t=t2-t1.
[0077] Table 2
[0078] Serial number Thermal conductivity / W / m*k Powder loss / mg Example 6 1580 1.3 Example 7 1740 1.6 Example 8 1610 1.2 Example 9 1820 0.9 Example 10 1490 1.3 Embodiment 11 1690 0.9 Comparative Example 6 1510 3.6 Comparative Example 7 1020 6.7 Comparative Example 8 960 4.2 Comparative Example 9 1470 3.8
[0079] It can be seen from the relevant test data in Table 2 that when the graphite film is prepared using the POD resin film of the embodiment of the present application, its thermal conductivity and powder loss are better than the comparative example. Among them, in comparative example 1, when the Ar2 group in the formed POD resin film is benzene, the corresponding graphite film has a higher powder loss. In comparative example 2, when the molecular structure of the POD resin film contains only the Ar1 group, the corresponding graphite film has a lower thermal conductivity and a higher powder loss. In comparative examples 3-4, when the ratio of Ar1, Ar2, and Ar3 in the molecular structure of the POD resin film is not within the range specified in the present application, its thermal conductivity and powder loss are inferior to the embodiments of the present application. It can be seen that the graphite film obtained using the embodiments of the present application has better thermal conductivity and powder loss performance. In addition, it can be seen from the relevant test data of Examples 6 and 11 that when the carbonization and graphitization process of the embodiments of the present application is adopted, a graphite film with better performance can be obtained. It is shown that the carbonization and graphitization process of the embodiment of the present application can help form a graphite film with a more complete structure.
[0080] The above are only specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A POD resin material, characterized in that: It comprises a repeating unit A, a repeating unit B and a repeating unit C, and the structures of the repeating unit A, the repeating unit B and the repeating unit C are as follows: Wherein, Ar1 is selected from a substituted or unsubstituted aromatic ring group of 6 to 20 carbon atoms; Ar2 is a substituted or unsubstituted aromatic ring group containing two benzene rings, and Ar1 and Ar2 are different; Ar3 is selected from a substituted or unsubstituted aromatic ring group of 6 to 20 carbon atoms, and at least one hydrogen in the aromatic ring group is substituted by a sulfonic acid group; The molar ratio of the number of moles of the repeating unit A to the sum of the number of moles of the repeating unit B and the repeating unit C is 99:1 to 70:30; The molar ratio of the repeating unit B to the repeating unit C is 1:1 to 2:
1.
2. The POD resin material according to claim 1, characterized in that: The Ar1 is selected from phenyl, biphenyl or naphthyl; the Ar2 is selected from biphenyl, naphthyl, Br-substituted biphenyl or Br-substituted naphthyl; the Ar3 is selected from phenyl, biphenyl or naphthyl substituted with sulfonic acid.
3. The POD resin material according to claim 1 or 2, characterized in that: In the POD resin material, the mass proportion of the C element is ≥40%, and the mass proportion of the S element is ≤10%.
4. The POD resin material according to any one of claims 1 to 3, characterized in that: The molar ratio of the benzene ring to the oxadiazole ring is 1:1.1 to 1:1.
5.
5. The POD resin material according to any one of claims 1 to 4, characterized in that: The POD resin material contains graphene; the mass proportion of the graphene in the POD resin material is 0.5%-50%.
6. A POD resin film, characterized in that: The POD resin film is prepared from the POD resin material according to any one of claims 1 to 5.
7. A method for preparing a POD resin film as claimed in claim 6, characterized in that: include: placing a reaction raw material including an aromatic diacid monomer, an aromatic diformic acid sulfonate and a hydrazine salt monomer in a fuming sulfuric acid solution for polymerization reaction to obtain a resin solution; The resin solution is subjected to film-forming treatment to obtain the POD resin film; The aromatic diacid monomers include at least some diphenyl ring aromatic diacid monomers, and the ratio of the total molar number of the aromatic diacid monomers and the aromatic diformic acid sulfonate to the molar number of the hydrazine salt is 1:1.01 to 1:1.
1.
8. The preparation method according to claim 7, characterized in that: The viscosity of the resin solution is greater than 100 Pa.S, and the solid content is 5-20%.
9. The preparation method according to claim 7 or 8, characterized in that: The aromatic diacid monomers include at least two of terephthalic acid, 1,4-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, 3,3-biphenyl dicarboxylic acid, terephthalic acid, 2,4-biphenyl dicarboxylic acid, 3,3-diphenyl ether dicarboxylic acid, isophthalic acid, biphenyl dicarboxylic acid, 2,6-naphthalene dicarboxylic acid or 1,4-naphthalene dicarboxylic acid; at least one of which is selected from biphenyl dicarboxylic acid, 2,6-naphthalene dicarboxylic acid or 1,4-naphthalene dicarboxylic acid; The aromatic dicarboxylic acid sulfonate includes isophthalic acid-5-sulfonate.
10. The preparation method according to any one of claims 7 to 9, characterized in that: The polymerization reaction comprises: Prepolymerize at 80-110°C for 2-5 hours, then heat to 110-170°C for polymerization for 2-5 hours.
11. A graphite film, characterized in that: The POD resin film according to claim 6 is obtained by carbonization and graphitization; the thickness of the graphite film is 0.01 mm to 100 mm, the thermal conductivity is ≥1300 W / m*k, and the surface powder loss is ≤2 mg.
12. The graphite film according to claim 11, characterized in that The carbonization temperature in the carbonization treatment is 800-1400° C., and the heating rate is 0.1-1° C. / min.
13. The graphite film according to claim 12, characterized in that: In the carbonization treatment, the heating rate is 0.4-0.8°C / min in the range of 800-1000°C; and the heating rate is 0.1-0.4°C / min in the range of 1000-1400°C.
14. An electronic device, characterized in that: It comprises a shell, a heating device and a graphite film as described in any one of claims 11 to 13, wherein the graphite film is arranged between the shell and the heating device.
Citation Information
Patent Citations
Sulfonated polyoxadiazole polymers articles
CN103261274A
Preparation of sulfonated polyoxadiazole polymers
CN103261275A
Aromatic polyoxadiazole, aromatic polyoxadiazole film and preparation method of aromatic polyoxadiazole film
CN112979947A
Production process for highly conductive graphitic films
US20150266739A1
Cited By
High-thermal-conductivity high-residual-carbon aromatic heterocyclic polymer-based graphite film and preparation method thereof
CN120535311A
A graphite film based on a high thermal conductivity and high carbon residue aromatic heterocyclic polymer and its preparation method
CN120535311B